2021
DOI: 10.3389/fcell.2020.615141
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Oligomerization and Its Relevance for Signaling by Receptors of the Tumor Necrosis Factor Receptor Superfamily

Abstract: With the exception of a few signaling incompetent decoy receptors, the receptors of the tumor necrosis factor receptor superfamily (TNFRSF) are signaling competent and engage in signaling pathways resulting in inflammation, proliferation, differentiation, and cell migration and also in cell death induction. TNFRSF receptors (TNFRs) become activated by ligands of the TNF superfamily (TNFSF). TNFSF ligands (TNFLs) occur as trimeric type II transmembrane proteins but often also as soluble ligand trimers released … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 151 publications
1
53
0
Order By: Relevance
“…Analyses of downstream apoptotic events, i.e., treatment-induced activation of caspase-3, an effector caspase with a central role in the process of cell apoptosis, revealed that RANK signaling also reduced the cleavage of procaspase-3 into its active form upon chemotherapeutic treatment: a significant reduction of active caspase-3 levels upon RANK stimulation was observed in the presence of both doxorubicin and cytarabine ( Figure 3 D; p = 0.002 and 0.031, respectively). Similar but less pronounced results were observed in all assay systems when non-clustered trimeric soluble hRANKL (sRANKL) instead of multimeric Fc-hRANKL was used to induce signals by RANK ( Supplementary Figure S1 ), in line with data, that for TNF family members in general and RANK in particular multimerization of ligands is required to obtain optimal signaling efficacy [ 28 , 29 ]. Altogether, our findings demonstrate that in AML cells signaling via RANK confers resistance to chemotherapy.…”
Section: Resultssupporting
confidence: 76%
“…Analyses of downstream apoptotic events, i.e., treatment-induced activation of caspase-3, an effector caspase with a central role in the process of cell apoptosis, revealed that RANK signaling also reduced the cleavage of procaspase-3 into its active form upon chemotherapeutic treatment: a significant reduction of active caspase-3 levels upon RANK stimulation was observed in the presence of both doxorubicin and cytarabine ( Figure 3 D; p = 0.002 and 0.031, respectively). Similar but less pronounced results were observed in all assay systems when non-clustered trimeric soluble hRANKL (sRANKL) instead of multimeric Fc-hRANKL was used to induce signals by RANK ( Supplementary Figure S1 ), in line with data, that for TNF family members in general and RANK in particular multimerization of ligands is required to obtain optimal signaling efficacy [ 28 , 29 ]. Altogether, our findings demonstrate that in AML cells signaling via RANK confers resistance to chemotherapy.…”
Section: Resultssupporting
confidence: 76%
“…The initiator caspases can then be further divided into whether they participate in the extrinsic or intrinsic apoptotic pathway. The extrinsic pathway involves caspase-8 and -10, which are activated by complexes like the death-inducing signalling complex (DISC) following binding of death ligands to their cognate receptors [ 14 , 15 ]. The intrinsic apoptotic pathway involves caspase-9, activated by the apoptosome following sensing of various intracellular signal like DNA-damage [ 16 , 17 ].…”
Section: Caspases…what's In the Name?mentioning
confidence: 99%
“…BAFF (also called BLys, TALL‐1, THANK, TNFSF13B, and CD256 145,146 ) is a type II transmembrane, homotrimeric protein that is expressed on the cell surface of myeloid cells (Table 2). 147‐149 It can also exist as a circulating soluble molecule that has been cleaved from the cell surface by a protease of the furin family 150‐154 . BAFF is a member of the tumor necrosis factor (TNF) family, 155 and its gene has been mapped to chromosome 13q32‐34 150 .…”
Section: Properties and Biological Actions Of Baffmentioning
confidence: 99%